PENGETAHUAN, TINGKAH LAKU, DAN TINDAKAN KLINIS DOKTER UMUM PADA PENATALAKSANAAN BPH - Adi, Kuncoro; Safriadi, Ferry; Sugandi, Suwandi; Haroen, Zulhardi; Noegroho, Bambang S; Tjahjodjati, Tjahjodjati (Indonesian Urological Association, 2008)
Objective: To evaluate the Primary Care Physician’s (PCPs) knowledge, attitude and clinical behavior in managing patients with BPH, as an input in the review of BPH guideline of Indonesian Urology Association. Material & method: The mailing included a cover letter, questioner consist of 10 questions survey, survey instrument and a post-paid envelope. A 10-questions survey were validated according to BPH guideline by Indonesian Urology Association (IUA). PCPs who work in district health offices and registered in district health office of Indonesian Health Ministry in Bandung, were selected as respondents. Results: 75% of sampled primary care physician working in 71 district health offices responded. 83% of respondent did not know the BPH guideline that had been published by Indonesian Urology Association. Although 88% of PCP’s knew about the symptoms of BPH, only 32% heard about of International Prostate Symptoms score. However, only 13 % were reported applying the symptoms score. Regarding to mandatory examination by the guideline, 64% of PCPs reported performing digital rectal examination, and 47% reported ordering urinalysis test. The recommended test such as PSA and serum creatinine level only asked 24% and 60% by PCPs. Only 21% of PCPs knew about the uroflowmetry but never ordering the test. 47% of PCPs reported using α blockers and 2% using finasteride for treating BPH. The referral was conducted by PCPs mostly due to urinary retention and hematuria. 70% of PCPs would refer the patients to urologist and the others to general surgeon and general internist. Conclusion: Although PCPs play role up to certain extent in diagnosing and managing of BPH, most of them are not interested in looking for reference.